2004
DOI: 10.1097/01.mot.0000142728.91330.94
|View full text |Cite
|
Sign up to set email alerts
|

Posttransplantation delirium: a review

Abstract: Purpose of reviewDelirium in hospitalized patients can increase costs and worsen postoperative outcomes, yet it is underdiagnosed and undertreated. Among transplant recipients with numerous features to monitor, the potential for this complication may be overlooked. An understanding of current concepts of delirium is helpful for posttransplantation monitoring and treatment of this vulnerable patient population. Recent findingsThis review summarizes the latest literature on mechanisms, risk factors, sequelae, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…In addition, we found that the presence and duration of delirium were predictive of longer hospital stays following transplantation. The finding that poorer pre-transplant cognitive function was associated with greater incidence of delirium is consistent with previous studies among individuals undergoing elective[12] and cardiac surgeries,[14] demonstrating that delirium is associated with longer hospital stays among older adults,[26] significant public health expenditures,[1] and a 3- to 11-fold increased 6-month mortality risk after controlling for disease severity. [2, 27] In addition, we have previously shown that poorer executive function is associated with greater incidence of delirium among individuals undergoing elective surgery independent of medical risk factors.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In addition, we found that the presence and duration of delirium were predictive of longer hospital stays following transplantation. The finding that poorer pre-transplant cognitive function was associated with greater incidence of delirium is consistent with previous studies among individuals undergoing elective[12] and cardiac surgeries,[14] demonstrating that delirium is associated with longer hospital stays among older adults,[26] significant public health expenditures,[1] and a 3- to 11-fold increased 6-month mortality risk after controlling for disease severity. [2, 27] In addition, we have previously shown that poorer executive function is associated with greater incidence of delirium among individuals undergoing elective surgery independent of medical risk factors.…”
Section: Discussionsupporting
confidence: 87%
“…Delirium is relatively common among hospitalized older adults and is associated with significant public health expenditures,[1] as well as 3- to 11-fold increased 6-month mortality risk after controlling for disease severity. [2] Delirium occurs in at least 20% of hospitalized older adults and may be even higher among post-transplant patients.…”
Section: Introductionmentioning
confidence: 99%
“…Delirium is common among hospitalized older adults and is associated with significant public health expenditures (38) and with a 3-to 11-fold increased 6-month mortality risk after controlling for disease severity (36). Delirium is also independently predictive of long-term neurocognitive impairment (25,39), and randomized trials are currently examining strategies to mitigate the negative impact of delirium (40).…”
Section: Discussionmentioning
confidence: 99%
“…Delirium is relatively common among hospitalized older adults and is associated with significant public health expenditures(3), as well as a substantially increased risk of 6-month mortality risk after controlling for disease severity(4). Available evidence suggests that the presence of delirium may also be associated with adverse cerebrovascular outcomes, similar to other surgeries(5, 6).…”
Section: Introductionmentioning
confidence: 99%